DECISION MAKING IN BUSINESS MODEL IMPROVEMENT OF INVESPROPERTI.ID USING KEPNER-TREGOE PERSPECTIVE (The Indonesian Journal of Business Administration, 2019)
InvesProperti.ID established in 2018 as fintech startup who provide a platform to aggregating ‘investors’ from society as lenders with property developers as borrowers in a Syariah crowdfunding scheme.  April, 14% of target has reached with details of 5 properties launched, 366 investors registered, and 1 billion rupiah managed which far below management’s expectation. Kepner-Tregoe analyses conducted to overcome concerns occurred. Situation appraisal determined condition and cause of underperforming business operation externally and internally. Some problems revealed, and top priority of concerns felt by management and interfere the business operation are no uniqueness in business model of InvesProperti.ID. Decision analysis will evaluate alternatives proposed to overcome problems which consist of improvements in customer segments, key activities, and key partners. Alternative also included with current business model to comparing the performance relative to other alternatives. Selecting an appropriate business model to improve current business model in financial and sustainability aspect is objective of alternative consideration. Objectives derived into ‘must’ and ‘want’ to evaluate available alternatives. Potential problems analysis will foresee consequences and prepare action to prevent or reduce them. Implementation will change some of resources needed in business operation such as investors relation, and improving function such as project supervisors, project analyst, and legal. Transition phase of implementation predicted will take 1-2 months before operation to do preparation such as improving capabilities of employee, and risk mitigation.Keywords:Business model improvement, decision making, financial technology, Kepner-Tregoe, property investment, Peer-to-Peer lending